Моделювання процесу пресування насіння рицини в шнекових пресах - Дідур, Володимир Володимирович; Журавель, Дмитро Павлович; Білоконь, Ярослав Володимирович; Didur, Volodymyr; Zhuravel, Dmytro; Bilokin, Yaroslav (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті запропоновано математичну модель процесу відтиску олії в шнековому пресі, побудовану на основі методів розмірного аналізу. Адекватність розробленої моделі підтверджено експериментальними результатами, отриманими під час пресування насіння рицини в шнековому пресі з використанням методів регресійного аналізу. Запропонована модель дає змогу описати витрату отриманої олії з урахуванням таких основних параметрів: швидкості подачі матеріалу, вологості сировини, ступеня лущення, температури в пресувальній камері, частоти обертання шнека, діаметра сопла для вивантаження макухи й тиску в зоні пресування. /// EN: The article proposes a mathematical model of the oil extraction process in a screw press, built on the basis of dimensional analysis methods. The adequacy of the developed model is confirmed by experimental results obtained during the pressing of castor seeds in a screw press, using regression analysis methods. The proposed model allows describing the consumption of the obtained oil taking into account the following main parameters: material feed rate, raw material moisture, degree of peeling, temperature in the pressing chamber, screw rotation frequency, diameter of the nozzle for unloading the cake and pressure in the pressing zone. Vegetable oil production occupies a leading place among the branches of world industry, which is due to the wide range of uses of vegetable oils in various spheres of economic activity. That is why the process of pressing oilseeds is the object of in-depth scientific research, in particular in terms of determining the factors that affect the efficiency of the press equipment. The main indicator of such efficiency is the amount of oil extracted from oilseeds. The productivity of a mechanical screw press, which is estimated by the degree of oil extraction from a particular type of oilseed, is largely determined by the method of its preparation. Preparation includes a set of separate technological operations, and also depends on the operating and design parameters of the pressing machine. In this work, a mathematical model of the process was developed based on the π-theorem of dimensional analysis. The proposed model allows describing the flow rate of the obtained oil taking into account the following main parameters: material feed rate, raw material moisture, degree of peeling, temperature in the pressing chamber, screw rotation frequency, diameter of the nozzle for unloading the cake and pressure in the pressing zone. Analysis of the graphical dependencies obtained from the results of mathematical modeling and regression processing of experimental data shows that the flow rate of the obtained oil increases with increasing material feed rate in the range of 0.006–0.014 kg/s. Increasing the p/n ratio also contributes to an increase in oil flow rate. In addition, it was found that the use of a nozzle of a smaller diameter ensures more intensive extraction of oil from oil raw materials.
Modeling of the process of pressing castor seeds in screw presses
Keywords: рослинна олія; насіння рицини; шнековий прес; швидкість подачі; математична модель; регресійний аналіз; vegetable oil; castor seeds; screw press; feed rate; mathematical model; regression analysis